Performance of Pharmaceutical Companies in India A Critical Analysis of Industrial Structure, Firm Specific Resources, and Emerging Strategies - Mazumdar, Mainak. (Contributions to Economics,, 2013)
This book explains how government support and institutional set up facilitated the evolution of the Indian pharmaceutical industry and provides an economic analysis of firm strategies due to recent policy changes. The book is useful for researchers interested in understanding the transition of a lifeline sector for an emerging economy like India. Students of public policy, health administrators and health economists who are interested in the functioning of the pharmaceutical sector that produces life saving drugs in developing nations will find this book useful. The book also provides good coverage on data envelopment analysis (DEA), a useful technique for understanding productivity and efficiency. It can provide guidance to the research students on the applicability of DEA technique to address various research questions for analysis. The book will be a valuable addition to libraries in colleges of pharmacy and medicine as well as to all other academic and research centers.